A Regional-Scale Assessment-Based SARS-CoV-2 Variants Control Modeling with Implications for Infection Risk Characterization - Yang YF; Lin YJ; You SH; Lu TH; Chen CY; Wang WM; Ling MP; Chen SC; Liao CM (Infection and Drug Resistance)
Ying-Fei Yang,1 Yi-Jun Lin,2 Shu-Han You,3 Tien-Hsuan Lu,4 Chi-Yun Chen,5,6 Wei-Min Wang,1 Min-Pei Ling,7 Szu-Chieh Chen,8,9 Chung-Min Liao1 1Department of Bioenvironmental Systems Engineering, National Taiwan University, Taipei, 10617, Taiwan; 2Institute of Food Safety and Health Risk Assessment, National Yang Ming Chiao Tung University, Taipei, 11230, Taiwan; 3Institute of Food Safety and Risk Management, National Taiwan Ocean University, Keelung City, 20224, Taiwan; 4Department of Science Education and Application, National Taichung University of Education, Taichung, 403514, Taiwan; 5Department of Environmental and Global Health, College of Public Health and Health Professions, University of Florida, Gainesville, FL, 32610, USA; 6Center for Environmental and Human Toxicology, University of Florida, Gainesville, FL, 32608, USA; 7Department of Food Science, National Taiwan Ocean University, Keelung City, 20224, Taiwan; 8Department of Public Health, Chung Shan Medical University, Taichung, 40201, Taiwan; 9Department of Family and Community Medicine, Chung Shan Medical University Hospital, Taichung, 40201, TaiwanCorrespondence: Chung-Min Liao, Department of Bioenvironmental Systems Engineering, National Taiwan University, No. 1, Sec. 4, Roosevelt Road, Taipei, 10617, Taiwan, Email cmliao@ntu.edu.twBackground: The emergence and progression of highly divergent SARS-CoV-2 variants have posed increased risks to global public health, triggering the significant impacts on countermeasures since 2020. However, in addition to vaccination, the effectiveness of non-pharmaceutical interventions, such as social distancing, masking, or hand washing, on different variants of concern (VOC) remains largely unknown.Objective: This study provides a mechanistic approach by implementing a control measure model and a risk assessment framework to quantify the impacts of control measure combinations on the transmissions of five VOC (Alpha, Beta, Delta, Gamma, and Omicron), along with a different perspective of risk assessment application.Materials and Methods: We applied uncontrollable ratios as an indicator by adopting basic reproduction number (R0) data collected from a regional-scale survey. A risk assessment strategy was established by constructing VOC-specific dose-response profiles to implicate practical uses in risk characterization when exposure data are available.Results: We found that social distancing alone was ineffective without vaccination in almost all countries and VOC when the median R0 was greater than two. Our results indicated that Omicron could not be contained, even when all control measure combinations were applied, due to its low threshold of infectivity (~3× 10− 4 plague-forming unit (PFU) mL− 1).Conclusion: To facilitate better decision-making in future interventions, we provide a comprehensive evaluation of how combined control measures impact on different countries and various VOC. Our findings indicate the potential application of threshold estimates of infectivity in the context of risk communication and policymaking for controlling future emerging SARS-CoV-2 variant infections.Keywords: SARS-CoV-2, variants of concern, basic reproduction number, modeling, non-pharmaceutical interventions, infection risk